254 Impact of sacubitril/valsartan on implantable defibrillator eligibility in heart failure: a real-world experience. (8th December 2021) - Monzo, Luca; Ferrari, Ilaria; Gaudio, Carlo; Cicogna, Francesco; Tota, Claudia; Petronilli, Valentina; Mennuni, Silvia; Ruvo, Ermenegildo De; Calò, Leonardo
Abstract: Aims: Current guidelines recommend an implantable cardiac defibrillator (ICD) in patients with symptomatic heart failure and reduced ejection fraction [HFrEF; left ventricular ejection fraction (LVEF) ≤35%] despite ≥3 months of optimal medical therapy. Recent observations demonstrated that sacubitril/valsartan induces beneficial reverse cardiac remodelling in eligible HFrEF patients. Given the pivotal role of LVEF in the selection of ICD candidates, we sought to assess the impact of sacubitril/valsartan on ICD eligibility and its predictors in HFrEF patients. Methods and results: We retrospectively evaluated 48 chronic HFrEF patients receiving sacubitril/valsartan and previously implanted with an ICD in primary prevention. We assumed that ICD was no longer necessary if LVEF improved >35% (or > 30% in asymptomatics) at follow-up. Over a median follow-up of 11 months, sacubitril/valsartan induced a significant drop in LV end-systolic volume (−16.7 ml/m 2, P = 0.023) and diameter (−6.8 mm, P = 0.022), resulting in a significant increase in LVEF (+3.9%, P < 0.001). As a consequence, 40% of previously implanted patients resulted no more eligible for ICD at follow-up. NYHA class improved in the 50% of population. A dose-dependent effect was noted, with higher doses associated to more reverse remodelling. Among patients deemed no more eligible for ICD, lower NYHA class [odds ratio (OR): 3.73 (95% CI: 1.05–13.24), P = 0.041], better LVEF [OR: 1.23 (95% CI: 1.01–1.48), P = 0.032], and the treatment with the intermediate or high dose of sacubitril/valsartan [OR: 5.60 (1.15–27.1), P = 0.032] were the most important predictors of status change. Conclusions: In symptomatic HFrEF patients, sacubitril/valsartan induced beneficial cardiac reverse remodelling and improved NYHA class. These effects resulted in a significant reduction of patients deemed eligible for ICD in primary prevention.